Effects of Epstein‐Barr virus viral load and different treatment modality for stage III nasopharyngeal carcinoma - Twu, Chih‐Wen; Wang, Wen‐Yi; Tsou, Hsiao‐Hui; Liu, Yi‐Chun; Jiang, Rong‐San; Liang, Kai‐Li; Lin, Po‐Ju; Lin, Tian‐Yun; Chen, Hsin‐Hong; Lin, Jin‐Ching (Head & neck, 2020)
Background We investigated treatment results, the effects of different treatment modality, and pretreatment Epstein‐Barr virus (EBV) viral load for stage III nasopharyngeal carcinoma (NPC) patients. Methods The initial definitive treatment for 356 stage III NPC patients consisted of concurrent chemoradiotherapy (CCRT) or induction chemotherapy plus radiotherapy (IndCT‐RT). The pretreatment EBV DNA level separated patients into a high (n = 106) or low (n = 250) viral load (≥ or < 1000 copies/mL) subgroup. Outcome measures include relapse rates and various survivals. Results The 5‐year rates of overall survival (OS), progression‐free survival (PFS), distant metastasis failure‐free survival (DMFFS), and locoregional failure‐free survival (LRFFS) were 88.6%, 83.0%, 90.5%, and 90.5%, respectively. Patient characteristics and pretreatment viral load between IndCT‐RT and CCRT were no significant differences except for a higher percentage of N2 disease in the IndCT‐RT subgroup. Both treatment modality resulted in similar relapse rates (P = .56), OS (P = .20), PFS (P = .53), DMFFS (P = .89), and LRFFS (P = .35). However, patients with a high viral load experienced a higher relapse rate (33.0% vs 12.4%, P < .001) and worse OS (5‐year rate, 79.0% vs 92.8%, P < .001), PFS (73.7% vs 88.4%, P < .001), DMFFS (80.2% vs 95.0%, P < .001), and LRFFS (85.6% vs 92.6%, P = .005) than those with a low viral load. Conclusion Long‐term treatment results for stage III NPC patients are rather good. IndCT‐RT can achieve the same treatment outcome as CCRT. Risk grouping by pretreatment viral load identified a subgroup (30%) of patients associated with a significantly higher relapse rates and worse survivals. These high‐risk patients need to strengthen treatment intensity in future trials.